Determination and investigation of mechanical behaviour on kenaf-sisal hybrid composite. (2021) - Vetre Selvan, E.; Ponshanmugakumar, A.; Ramanan, N.; Naveen, E.
Abstract: Technological development in automobile & aerospace industries make us to develop new materials that have high strength to weight ratio, good mechanical characteristics and better corrosion resistance. Composite materials fulfill the above requirements. In this project, hybrid composites are fabricated in which natural fiber is used as a reinforcement and the epoxy resin along with hardener & Graphene are used as a matrix. Kenaf and Sisal fiber are used for fabricating the hybrid composite. Compression moulding process is used for fabricating the composites in which machine is maintained at 120 degree celsius as curing temperature and pressure for 10 bar for 2–3 h. Three Samples such as (kenaf - kenaf), (sisal - sisal), (kenaf - sisal) combinations were fabricated namely composite 1, composite 2, and composite 3 respectively. Testing such as tensile, flexural, impact and wear are performed on three composites. It is found that composite 3 has better mechanical behavior as compared to other composites as Tensile strength of 156 Mpa, and Flexural strength of 282 Mpa. Impact test value remains same for all the composites. Micro-structural analysis was performed by using scanning electron microscope to explain the failure mechanisms and behaviour of the composites